2.6x-86=1.5x+2

Simple and best practice solution for 2.6x-86=1.5x+2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2.6x-86=1.5x+2 equation:


Simplifying
2.6x + -86 = 1.5x + 2

Reorder the terms:
-86 + 2.6x = 1.5x + 2

Reorder the terms:
-86 + 2.6x = 2 + 1.5x

Solving
-86 + 2.6x = 2 + 1.5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1.5x' to each side of the equation.
-86 + 2.6x + -1.5x = 2 + 1.5x + -1.5x

Combine like terms: 2.6x + -1.5x = 1.1x
-86 + 1.1x = 2 + 1.5x + -1.5x

Combine like terms: 1.5x + -1.5x = 0.0
-86 + 1.1x = 2 + 0.0
-86 + 1.1x = 2

Add '86' to each side of the equation.
-86 + 86 + 1.1x = 2 + 86

Combine like terms: -86 + 86 = 0
0 + 1.1x = 2 + 86
1.1x = 2 + 86

Combine like terms: 2 + 86 = 88
1.1x = 88

Divide each side by '1.1'.
x = 80

Simplifying
x = 80

See similar equations:

| x-12.50+0.1x=0.2 | | 9.8=5x+8.5 | | 6.5x+8-3.5x=5 | | -4y+7=27 | | y^4+2x^2-4xy=-2 | | -5(9a+6)= | | 0.5x+0.1=1.9 | | 2x+15=15x+13 | | 2(x-7.1)=9.4 | | -5=-5+d | | 6x+8.57=3x+14 | | a+18=75 | | 31.82-2y=-4.5+3.92 | | x^2-5x-14=17 | | -9b^2+8b-8=0 | | 3x1/3= | | 4ln(3x-5)3=18 | | -20x+29=20x+29 | | (x-7)(x+2)=17 | | 19x+16=86 | | p-13=31 | | a(x)+b=c | | 7e-4(6+2w)=3(w-8) | | -4(5x-7)+1=20x+29 | | 25x+20=78 | | 47x=46x+1 | | 60+4n=76 | | 40x+18=86 | | 3(x+2)-8x=4x+1 | | 20x-10=110 | | 30x-18=150 | | 12=v+2 |

Equations solver categories